Violence in schools : the response in Europe - Smith, Peter K. (RoutledgeFalmer, 2003)
Having researched the topic of violence in schools for over a decade, Peter K. Smith brings together accounts of school violence from a wide range of European countries in his new book, Violence in Schools.